Treatment Interruptions During Stereotactic Body Radiotherapy for Prostate Cancer - Abigail N. Pepin; Alan Zwart; Malika Danner; Marylin Ayoob; Thomas Yung; Brian T. Collins; Deepak Kumar; Simeng Suy; Nima Aghdam; Sean P. Collins (Frontiers in Oncology, 2022)
BackgroundDuring the course of radiation treatment for prostate cancer, patients may have unintentional interruptions in their treatment course due to a wide variety of factors. Stereotactic body radiation therapy (SBRT) decreases the number of treatments compared to conventionally fractionated radiation; hence, it has the potential to decrease treatment delays and non-completion. This study sought to determine the incidence of treatment delay and characterize the etiology and length in a large cohort of men treated with SBRT for their prostate cancer.MethodsOne thousand three hundred and thirty-six patients treated with SBRT from 2008 to 2021 at the Georgetown University Hospital for prostate cancer were included in this retrospective study. A treatment delay was defined as a patient requiring longer than 14 days to complete 5 fractions of SBRT. Non-completion was defined as patients treated with less than 5 fractions. In the patients who experienced delays, chart review was performed to characterize the length and etiology of each delay. Multivariate analysis was performed via binary logistic regression modeling on PSPP.ResultsAll individuals in the cohort eventually completed the planned 5-fraction regimen. Thirty-three patients experienced a treatment delay. Median length of time to complete treatment was 11 days (range 5–155 days). In patients who experienced a delay, nearly half (45.5%) experienced only a one-day delay. The most common reason for a delay was a technical issue (48.5%), including the machine maintenance, fiducial misalignment, or inadequate pretreatment bowel preparation. Other reasons included unplanned breaks due to acute side effects (21.2%), logistical issues (18.2%), non-treatment related health issues (9.1%), and inclement weather (3.0%). There were no significant sociodemographic, oncologic, or treatment variables that predicted treatment interruption on multivariate analysis.ConclusionsThe incidence of treatment interruptions in patients undergoing SBRT for their prostate cancer was low. Most treatment delays were short.